A New Printable Alginate/Hyaluronic Acid/Gelatin Hydrogel Suitable for Biofabrication of In Vitro and In Vivo Metastatic Melanoma Models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2022)
Two-dimensional (2D) cancer models have been the standard for drug development over the past few years, but they frequently do not resemble in vivo properties adequately. 3D models are superior in many aspects and are, therefore, more similar to human pathophysiology. Over the past years, the emerging field of biofabrication has made significant advances, resulting in even more sophisticated 3D models. With this study, a hydrogel is created for biofabrication that is suitable for mimicking the tumor microenvironment in vitro and is further tested as a new vascularized melanoma model in vivo. The alginate/hyaluronic acid/gelatin bioink shows good shape-fidelity, high cell survival rates, and enables successful cultivation of melanoma cells and adipose-derived stem cells as well as cell differentiation in vitro. In vivo, in the arteriovenous loop model, it proves to be a unique method to study melanoma progression, tumor vascularization, and ultimately and reliably metastases in an isolated and controlled environment. These results show that this 3D model is very application-oriented for molecular research and therapy development.
CRIS-Team Scopus Importer:2021-10-22
Keywords: bioinks; metastasis; stem cells; tissue engineering; tumors